Rancang Bangun dan Pengujian Sistem Reaktor Plasma Lucutan Pijar Korona guna Mempercepat Pertumbuhan Tanaman Mangrove - Triadyaksa, Pandji; Nur, Muhammad; Nasrudin, Nasrudin; Wasiq, J. (BERKALA FISIKA, 2007)
Plasma glow discharge corona reactor system has been made and tested to stimulate mangrove growth. Plasma glow discharge corona reactor consists of DC high voltage system and point to plate electode system. Reactor performance test has done on Rhizophora apiculata mangrove species. High voltage system mainly develop using TV fly back that been triggered by pulsed frequency using oscillator circuit. Point to plane electrode system was designed to maintain two electrode range remains 3 cm with number of point electrode plugged parallel with plane electrode are 63 pieces. Plasma glow discharge corona reactor testedÂ was done on radiation process of mangrove seed by divided sample groups into 6 sample which have different time radiation and 1 sample that not been radiated as a control data. Mangrove growth was analyzed by measure the growth of mangrove plumulae after 17 days of cultivation. Research results shows that in developing plasma glow discharge corona to radiate mangrove, plasma reactor system works in 8 kV DC plasma voltage development. Mangrove growth after 6 time variation of plasma radiation shows a good effect of growth stimulation along with longer radiation time duration.Â The increase of mangrove growth was hypothetically caused by an increase of nitrogen concentration in mangrove seeds because of ion nitrogen fixation in the seeds during plasma radiation process